Iqbal Commentary of Sūrat al-Ikhlāṣ - Mir, Mustansir (Intellectual Discourse, 2013)
In the concluding part of Rumuz-i Bikhudi, Iqbal offers a commentary (tafsir) on the 112 sūrah of the Qur’ān. While not a Qur’ānic commentary in the conventional sense of the term, Iqbal's discussion of the individual verses of the sūrah seeks to bring out the practical and social implications of the Islamic message of the oneness of God (tawḥīd): Divine unity should teach Muslims the lesson of social cohesion; God's being the Refuge should lead them to put their trust in God and reject fatalism; that God neither begets nor is begotten should make them repudiate lineage as the basis of unity; and God's uniqueness should encourage them to become matchless among the world's nations. Tawḥīd, in other words, ought to become the controlling principle in the actual life of Muslims. Hortatory in character, Iqbal's tafsir of the Qur’ānic sūrah is integrally related to the general philosophy of life and society that Iqbal presents in his works.